SPATIO-TEMPORAL CLUSTER ANALYSIS OF DISEASE - M. S. Abramovich; S. V. Anishchanka; M. M. Mitskevich; O. I. Bydanov (Informatika)
The robust version of the spatial scanning statistics for clustering is proposed. Spatio-temporal cluster analysis algorithms were used for the cluster detection of incidence of thyroid carcinoma. Me-thods and algorithms of detection and building clusters for disease on studying territories are consi-dered.